Determination of least-cost nutritionally adequate diets for families in Bicol region by linear programming - Ericta, Hazel Dancel
By means of the linear programming method, least-cost diets for 246 families in Bicol Region were determined. Using prices in March, 1974, the least cost of meeting the daily nutritional objectives of the families ranged from PHP 0.76 to PHP 1.22 or an average of PHP 0.98. On the other hand, the least cost of satisfying both the nutritional and cultural objectives of the families ranged from PHP 0.93 to PHP 1.40 or an average of PHP 1.13. The families could meet their daily recommended allowances in the most economical way by incorporating in their diets "gabi" leaves, "malunggay" leaves, "miki", rice and brown sugar. At the same time, they can take into account some cultural considerations by including in addition to these foods, fish, specifically, smoked "galunggong" or fresh "dilis", A change in price during the seven-month interval caused an average increase of 44 percent in the cost of least-cost diets. However, it did not affect the composition of least-cost diets in a major way. A least-cost diet using March, 1974 prices and including both nutritional and cultural constraints was determined for a standard family. The composition of such a diet was found to be very similar in composition to that of the diets of the actual families. Among the nutrients studies, riboflavin had the highest marginal cost while vitamin A had the lowest.